Exploring the Role of Reviving Decorative Motifs in Contemporary Hausa Traditional Architecture towards Preserving Cultural Identity: A Case Study of Gidan Shettima Kano Emirate Council - Umar Salim, Bashir; Shaheed Faruk Sarkinfada (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Hausa decorative motifs are integral to the architectural and artistic heritage of the Hausa people. Traditional Hausa architecture faces challenges in maintaining cultural continuity amidst modern architectural practices that often overlook traditional elements. This study investigates the role of reviving decorative motifs in preserving cultural identity within Hausa traditional architecture, focusing on Gidan Shettima in the Kano Emirate Council. A qualitative methodology was employed, involving in-depth interviews with master builders, artisans, and cultural experts, alongside architectural analysis and visual documentation. The findings revealed that decorative motifs in Hausa architecture originated over 900 years ago, with primary types including Dagi (emblem/logo), Sarka (chain), and Zanen zayyana (calligraphy). These motifs have evolved with changes in materials and techniques but remain integral in preserving Hausa cultural identity. Key motifs like Sarka are prevalent in Gidan Shettima. The study underscores the importance of these decorative elements in maintaining cultural heritage. Recommendations include documentation and preservation efforts, training programs for artisans, community involvement, integrating modern and traditional techniques, policy development, and further research. By implementing these recommendations, stakeholders can ensure the continued celebration and preservation of Hausa cultural identity through architectural motifs.